Zyklus-Apps zur Verhütung - sicher oder Gesellschaftsspiel? - Frank-Herrmann, Petra; Freis, Alexander; Strowitzki, Thomas (Der Gynäkologe, 2019)
This paper gives an overview of currently available cycle apps which indicate the fertile window of the menstrual cycle. Forecast apps, i. e., apps predicting the fertile window based on data of previous cycles (cycle lengths, previous temperature rises) are useless for contraception. Actually, highly effective family planning still needs evidence-based variations of the symptothermal method (see guidelines of the Section Natural Fertility of the German Society of Gynecological Endocrinology and Reproductive Medicine, DGGEF). However, corresponding apps need effectiveness studies according to scientific criteria as well. Apps which are associated with measuring systems (hormones in urine or saliva or new parameters like pulse rate) have not yet met the expectations because no parameter with the necessary accuracy has been found. The US Federal Drug Administration approval of the forecast app Natural Cycles is scientifically not understandable.
Online publiziert: 20. November 2018
Gesehen am 06.08.2019